2021
DOI: 10.1038/s41598-021-94708-1
|View full text |Cite
|
Sign up to set email alerts
|

AZP2006, a new promising treatment for Alzheimer’s and related diseases

Abstract: Progranulin (PGRN) is a protein with multiple functions including the regulation of neuroinflammation, neuronal survival, neurite and synapsis growth. Although the mechanisms of action of PGRN are currently unknown, its potential therapeutic application in treating neurodegenerative diseases is huge. Thus, strategies to increase PGRN levels in patients could provide an effective treatment. In the present study, we investigated the effects of AZP2006, a lysotropic molecule now in phase 2a clinical trial in Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Helping to keep or bring glial cells back into this clearance and phagocytosis stage before the activation and pathology worsening phase, as the PEL24-199 molecule seems to do, could thus be an interesting therapeutic strategy. These results are consistent with a recently published study showing that AZP2006, a related compound, possessed neuroprotective properties in two animal models of AD and aging [ 75 ]. Thus, the beneficial effects of AZP2006 were linked to the inflammation regulator progranulin and the inhibition of TLR9 receptors that are normally responsible for proinflammation when activated.…”
Section: Discussionsupporting
confidence: 93%
“…Helping to keep or bring glial cells back into this clearance and phagocytosis stage before the activation and pathology worsening phase, as the PEL24-199 molecule seems to do, could thus be an interesting therapeutic strategy. These results are consistent with a recently published study showing that AZP2006, a related compound, possessed neuroprotective properties in two animal models of AD and aging [ 75 ]. Thus, the beneficial effects of AZP2006 were linked to the inflammation regulator progranulin and the inhibition of TLR9 receptors that are normally responsible for proinflammation when activated.…”
Section: Discussionsupporting
confidence: 93%
“…P-Tau protein accumulation may be influenced by decreasing Psap levels and their interactions in neurons [ 72 ]. Other studies have suggested that Psap may play a role in Alzheimer’s disease [ 73 , 74 , 75 ]. Psap has also been linked to neurotrophic and cell-damaging effects [ 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…AZP2006, a small molecule and lead compound of the piperazine family, is another potential treatment that is being studied for its efficacy in treating AD and other related disorders, including PSP. In a study published in 2021, AZP2006 increased levels of the protein progranulin (PGRN) [127]. PGRN is a glycoprotein that is secreted or transported to lysosomes in neurons and the immune system [127].…”
Section: Anti-inflammatory Therapiesmentioning
confidence: 99%
“…In a study published in 2021, AZP2006 increased levels of the protein progranulin (PGRN) [127]. PGRN is a glycoprotein that is secreted or transported to lysosomes in neurons and the immune system [127]. It is associated with regulating neuroinflammation, neurite branching and outgrowth, lysosome function, and neuron survival [127].…”
Section: Anti-inflammatory Therapiesmentioning
confidence: 99%
See 1 more Smart Citation